Rethinking resilience as capacity to endure: automobility and the city - Schwanen, T (Routledge, 2016)
Now resilience has become one of the decade's buzzwords, urban scholars cannot afford to renounce or abandon it; they should reclaim it for critical purposes. This piece offers one way of doing this, by moving away from socio-ecological systems thinking and reworking some concepts elaborated by Alfred North Whitehead. It proposes that resilience be seen as the capacity of a configuration of elements to endure through an intricate mixture of stability and change. This capacity emerges from this configuration's entanglements with its environment and from symbiosis, friction and contestation. The conceptualisation is subsequently utilised to caution against over-optimism about the post-automobile city. The continuing dominance of the privately owned internal combustion engine, the neutralising absorption of car sharing by the car industry and the current enthusiasm over autonomous cars are reinterpreted as manifestations of automobility's capacity to endure through adaptation and influence over its environment. The socio-spatial inequalities and injustices associated with automobility are likely to persist through change as well.